2013
DOI: 10.1002/phar.1258
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid and Nicotinamide: A Review of Their Use for Hyperphosphatemia in Dialysis Patients

Abstract: Phosphate binders have traditionally been used to treat hyperphosphatemia, a common complication in patients with end stage renal disease (ESRD). New evidence suggests that nicotinic acid and its metabolites may effectively decrease phosphorus absorption in the gastrointestinal tract, thereby reducing serum phosphorus concentrations. We conducted a literature search to identify studies of patients with ESRD on dialysis that evaluated the role of niacin and related compounds in decreasing serum phosphorus level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Recruiting patients with a higher phosphorus level at baseline may help researchers to readily identify the significance of hypophosphatemic effects of interventions. 34 To evaluate the sustainability of niacinā€™s therapeutic effects, long-term follow-up of patients is recommended. Lastly, potential confounders, such as dietary phosphorus intake, other phosphate binder use, and concurrent statin therapy, are required to be adequately controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Recruiting patients with a higher phosphorus level at baseline may help researchers to readily identify the significance of hypophosphatemic effects of interventions. 34 To evaluate the sustainability of niacinā€™s therapeutic effects, long-term follow-up of patients is recommended. Lastly, potential confounders, such as dietary phosphorus intake, other phosphate binder use, and concurrent statin therapy, are required to be adequately controlled.…”
Section: Discussionmentioning
confidence: 99%
“…128,129 Moreover, a number of practical measures have the potential to moderate serum phosphate levels by minimizing the amount of phosphate absorbed from the diet: choosing a plant-based diet, in which a high proportion of the phosphate is tied up in poorly absorbable phytates; avoiding soft drinks and processed foods that contain phosphate additives; employing phosphate-binding drugs such as sevelamer or lanthanum carbonate, as is commonly done in treatment of chronic renal disease; magnesium supplementation; and treatment with sustained-release niacin, which appears to decrease gastrointestinal expression of a prominent phosphate transport protein. [128][129][130][131][132][133][134][135][136][137][138][139][140] Vitamin K and Vitamin D Vitamin K can favorably influence VC, as posttranslational Ī³-carboxylation of MGP, catalyzed by a vitamin K-dependent enzyme, is crucial to MGP's ability to antagonize VC. 141,142 This presumably explains why use of the vitamin K-antagonist drug warfarin is associated with increased risk for VC.…”
Section: Minimizing Phosphate Absorptionmentioning
confidence: 99%
“…Additionally, the kinetics of niacin supplementation in dairy cows is not completely clear. In humans, the maximal plasma concentration of nicotinic acid is reached after 30-60 min when administered orally (22) , and the plasma half-life of nicotinic acid is about 20-45 min, whereas the half-life of nicotinamide is about 4 h (23) . In dairy cows, the half-life of nicotinamide could probably be longer than 4 h, because Zimbelman et al (18) found the serum niacin concentration returned to presupplementation values by 3 d after a dose of 12 g/d RPN supplementation.…”
Section: Niacin Sources and Bioavailabilitymentioning
confidence: 99%